(untitled) (UMRAN - Journal of Islamic and Civilizational Studies, 2016)
The formation of highly noble morale based on Islamic law is very important in creating an ideal personality. Since every human being has different personalities and behavior, it is necessary for us to refine the issues pertaining to a various of human personality. Thus, this paper aims to discuss the concepts’,key and the sources of personality based on Al-Quran and Sunnah. In reality, the lack understanding in defining the personality traits has resulted in the existence of various problems, subsequently affecting the relationship and daily interaction among people. Therefore, the ability to practice personality trait in a consistent way based on Islamic principles is a benchmark in producing of positive work values. To a gerater degree, the understanding the concept of personality based on the Islamic perspective, should be able help us to lead a better in the world and be closer to Allah as the Creator of the world in our journey towards the Hereafter.